Gastric Mucous Atrophy and Metaplasia in Patient with Helicobacter pylori Infection - Nikko Darnindro; Ari Fahrial Syam; Diah Rini Handjari; Dadang Makmun (The Indonesian Society for Digestive Endoscopy, 2015)
Background: Helicobacter pylori (H. pylori) is one of the most common bacteria found in human and cause chronic infection. Recent study conducted in one of private hospitals in Jakarta shows that there is a trend of declining prevalance of H. pylori from 12.5% in 1998 to 2.9% in 2005. The aim of this study is to obtain` the prevalance of gastric atrophy and metaplasia in patients with H. pylori infection based on histopathology.Method: This was a case control study between June to August 2014 with 69 cases and 71 controls using medical records datas and histopathology results. Control sample was taken consecutively from patient undergone esophagogastroduodenoscopy procedure in 2013.Results: The average age for patient with H. pylori was 51 years slightly higher than patient with negative H. pylori (p 0.05). Generally, the prevalence rate among males was slightly lower than females (p 0.05). From Histopathology findings, active chronic gastritis was found in 62.3% patients with positive H. pylori than only 12.7% in patient with negative H. pylori (95% CI = 4.86-26.7; OR = 11.31). Mild and moderate atrophy was higher among H. pylori positive (p = 0.09). gastric mucous metaplasia was also higher (10% vs. 1.4%) among positive H. pylori patient (p = 0.03).Conclusion: H. pylori infection can cause atrophy and metaplasia in gastric mucosa. Prevalence of gastric metaplasia caused by H. pylori infection is lower in this study compared to the same study abroad.